Análise dos metabólitos secundários de isolados de trichoderma em células CALU-3 e em Pseudomonas aeruginosa - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Fungi of the Trichoderma species are highly specialized in surviving symbiotically through endophytic activities inhabiting the interior of plant tissues. In addition, these microorganisms have substances described as secondary metabolites, which are being increasingly detected as biological materials, with the aim of being substances of biotechnological potential, with antibiofilm, cytotoxic activity, among others. Therefore, this work aimed to carry out an analysis of secondary metabolites of Trichoderma isolates. For these activities, 10 Trichoderma species named 18, T00, 57, 46, B102, AB302, AM201, AB107, S404 and ALL42 had their secondary metabolites investigated. With the lethality assays in Artemia salina, it was possible to evaluate the secondary metabolites of the Trichoderma isolates with conversion into the mean lethal concentration (LC50), thus, of the ten secondary metabolites of the Trichoderma isolates, six of which were named 18, T00, 46, B102 and AM201 adopted LC50 toxicity. However, the author, considering the metabolites of the Trichoderma isolates that demonstrated LC50 with a concentration of up to 100 µg.ml1, thus excluding the AM201 isolates, stipulated a cut-off point. Isolated B102 showed high toxicity and was not selected. Thus, only the secondary metabolites of the Trichoderma isolates called 18, T00 and 46 were selected for cytotoxicity or cell viability assays by the MTT method and evacuation of biofilms of Pseudomonas aeroginosa strains. The results of cell viability show that the secondary metabolites of the isolates showed a decrease between 13 and 20%, even though there was no regularity in the reduction of viability between the concentrations used in all the metabolites of the isolates. The antibiofilm activity of the secondary metabolites of the Trichoderma isolates against the biofilms produced by Pseudomonas aeruginosa strains revealed that the secondary metabolites of the three isolates used (18, T00 and 46) were very efficient in those strains of P. aeruginosa categorized according to formation of biofilm as strong.
Analysis of secondary metabolites of trichoderma in CALU-3 cells and Pseudomonas aeruginosa
Keywords: Trichoderma spp; Moléculas bioativas; Formação de biofilme; Trichoderma spp; Bioactive molecules; Biofilm formation; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::IMUNOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA